A novel thiourea loading strategy for improving the moisture resistance of K2SiF6: Mn4+ red phosphors. (July 2023) - Pan, Xixiang; Wu, Di; Liu, Songbin; Zhou, Qiang; Song, Biqing; Wen, Lu; Luo, Li; Wang, Jie; Ye, Xinyu
Highlight: A novel thiourea loading strategy was proposed to modify KSF phosphor. The excellent water resistance was obtained after thiourea treatment. The degradation and restore mechanisms of T-KSF phosphor was revealed. Abstract: Recently, Mn 4+ doped fluoride phosphors have been considered as ideal candidate materials employed in white light-emitting diodes (WLEDs). However, the extremely serious performance deterioration in a wet environment has affected their practical commercial applications. Herein, we developed a novel thiourea loading strategy for greatly improving the moisture resistance of typical K2 SiF6 : Mn 4+ (KSF) red phosphors through treated by thiourea ethanol solution evaporation. The luminescent properties and moisture resistance have been discussed in detail, and the underlying moisture resistance mechanism was further proposed. The results show that the moisture resistance of KSF phosphor treated by thiourea significantly increased approximately sevenfold than that of untreated counterpart, exhibiting a potential application in the WLEDs backlight with high gamut display. These works brings up a promising alternative strategy for enhancing moisture resistance and provides a deeper understanding on the performance degradation mechanism for a variety of Mn 4+ doped fluoride phosphors system. Graphical abstract: Image, graphical abstract